Carbon catabolite repression by seryl phosphorylated HPr is essential to Streptococcus pneumoniae in carbohydrate‐rich environments. Issue 2 (15th May 2015) - Fleming, Eleanor; Lazinski, David W.; Camilli, Andrew
Summary Carbon catabolite repression (CCR) is a regulatory phenomenon implemented by bacteria to hierarchically organize carbohydrate utilization in order to achieve maximal growth. CCR is likely of great importance to Streptococcus pneumoniae because the human host sites inhabited by this pathogen represent complex carbohydrate environments. In this species, inactivation of the prototypical Gram‐positive CCR master regulator, ccpA, attenuates virulence in mice but does not relieve CCR of most metabolic enzymes, suggesting CcpA‐independent CCR mechanisms predominate. Here we show the activities of three transcriptional regulators constitute the majority of transcriptional CCR of galactose metabolism operons. We determined seryl‐phosphorylated histidine phosphocarrier protein (HPr‐Ser∼P)‐mediated regulation is a major CCR mechanism and an essential activity in the pneumococcus, as an HPr point mutation abolishing HPrK/P‐dependent phosphorylation was not tolerated nor was deletion of hprk/p. The HPr‐Ser∼P phosphomimetic mutant HPr S46D had reduced phosphotransferase system transport rates and limited induction of CCR‐repressed genes. These results support a model of pneumococcal CCR in which HPr‐Ser∼P directly affects the activity of CcpA while indirectly affecting the activity of pathway‐specific transactional regulators. This report describes the first CcpA‐independent CCR mechanism identified in the pneumococcus and the first example of lethality from loss of HPr‐Ser∼P‐mediated CCR in any species.